2001
DOI: 10.1677/joe.0.1700539
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diethylstilbestrol on cell proliferation and expression of epidermal growth factor in the developing female rat reproductive tract

Abstract: To evaluate mechanisms of cell proliferation in the fetal female rat reproductive tract, diethylstilbestrol (DES) effects on cell division and estrogen receptor (ER), epidermal growth factor (EGF) and EGF receptor (EGF-R) expressions were determined from gestational day (GD) 15·5 to 21·5. Reproductive tracts were evaluated within three regions along the Müllerian duct axis; these were proximal, middle and caudal, which differentiate into oviduct, uterus and upper vagina respectively. In fetuses from non-treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 72 publications
1
18
0
Order By: Relevance
“…Indeed, autoradiography revealed extensive binding by [ 3 H]DES in mouse reproductive tract on GD 17 following transplacental exposure (Holderegger & Keefer 1986). In our previous report, we suggested that DES may act mainly via ER , since DES down regulated ER 1 and ER 2 mRNAs, but not ER mRNA (Okada et al 2001). Based on the present findings, however, transplacental exposure to estrogen agonists including DES may act in the Müllerian duct via dominantly expressed ER .…”
Section: Discussionsupporting
confidence: 43%
“…Indeed, autoradiography revealed extensive binding by [ 3 H]DES in mouse reproductive tract on GD 17 following transplacental exposure (Holderegger & Keefer 1986). In our previous report, we suggested that DES may act mainly via ER , since DES down regulated ER 1 and ER 2 mRNAs, but not ER mRNA (Okada et al 2001). Based on the present findings, however, transplacental exposure to estrogen agonists including DES may act in the Müllerian duct via dominantly expressed ER .…”
Section: Discussionsupporting
confidence: 43%
“…DES exposure of prenatal mice has been shown to cause various abnormalities, including those in the thymus, skeletal tissues, female reproductive organs, and muscles (Takasugi, 1963;Maier et al, 1985;Okada et al, 2001). In the thymus, prenatal exposure to DES has been shown to cause thymic atrophy and several other changes, such as apoptosis, T cell differentiation, immunotoxicity, and immunosuppression (Ford et al, 1983;Brown et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…In developing mice and rats, ER is expressed in oviductal epithelial and stromal cells, but ER is absent in both cell types (Yamashita et al 1989, Li 1994, Mowa & Iwanaga 2000, Okada et al 2002a, 2003. Pre-and neo-natal exposure to diethylstilbestrol (DES), a synthetic estrogen, caused abnormal morphology and altered cell proliferation in mouse and rat oviducts (Newbold et al 1983, Okada et al 2001. However, the oviduct of mice lacking ER was resistant to neonatal DES exposure (Couse et al 2001) indicating an essential role of ER in mediating the estrogen effect on developing neonatal oviduct.…”
Section: Introductionmentioning
confidence: 99%